The implementation of a PDR 3D-guided gynaecological brachytherapy service in a UK centre. Issue 3 (19th August 2013) - Wood, D.; Lane, L.; Gillespie, W.; Baker, S.; Rowbottom, C.
Abstract Background Due to the discontinuation of the widely used low-dose rate (LDR) Caesium afterloader units, many centres in the past 10 years have moved from LDR Selectron treatments to Iridium 192 afterloaders. While the majority of UK centres have opted for high-dose rate (HDR) units, the Christie have invested in two pulsed dose rate (PDR) afterloaders alongside a move to full 3D-planned gynaecological brachytherapy. Purpose To share the experience and learning curve involved in the implementation of a 3D-guided PDR brachytherapy service. Methods The specific logistical and practical challenges of implementing a PDR service are discussed alongside the more general challenges of implementing 3D-guided magnetic resonance (MR) based brachytherapy. A multidisciplinary approach was undertaken to streamline the patient pathway and give all disciplines a forum to discuss service improvements and resolve problems. Conclusions The lessons learned throughout this experience can inform the decisions of departments that may wish to implement a PDR service or indeed a 3D image-guided HDR brachytherapy service in the future. The focus on the utilisation of lean principles to the patient pathway, improved multidisciplinary working and enhancing service efficiency is of interest to all centres.